Using Langlol to teach Vocabulary and Values in an English as a Second Language Classroom - Yumnam, Rosy (Selangor Humaniora Review, 2021)
The teaching and learning of vocabulary are an important aspect of the language learning process. Vocabulary is often developed through reading. Relatedly, values form a vital part of the life of an individual. Vocabulary can be taught through learning to read the content, which is replete with values. In this context, the paper employs the Content-Based Instruction (CBI) Approach to incorporate the teaching of vocabulary and values in an English as a Second Language (ESL) classroom. In CBI Approach, the use of authentic material plays an important role in the language learning process. The paper explores the various possibilities of using Langlol, an indigenous moral discourse of Manipur, a state in Northeast India, as the main teaching material to integrate the teaching of vocabulary and values. The study was conducted with the students of one of the schools of Manipur. The findings of the study indicated that the CBI approach using the indigenous material assisted in developing vocabulary as well as understanding values.